The effect of berberine adjunctive treatment on glycolipid metabolism in patients with schizophrenia: A randomized, double-blind, placebo-controlled clinical trial. (June 2021) - Li, Meijuan; Liu, Ying; Qiu, Yuying; Zhang, Jing; Zhang, Yonghui; Zhao, Yongping; Jia, Qiong; Li, Jie
Highlights: Berberine may reduce dyslipidemia and improve insulin resistance in schizophrenia patients. Baseline BMI and serum prolactin may predict the effect of berberine on improving insulin resistance Abstract: Previous studies have shown that berberine can improve metabolic disturbances in non-psychiatric patients, but no clinical research has been conducted in schizophrenia. This study was a randomized, double-blind, placebo-controlled clinical trial. Eligible patients diagnosed with schizophrenia were randomized to receive placebo or berberine (900mg/day) as an adjunctive treatment for eight weeks. Peripheral glycolipid metabolism parameters were measured at baseline, week 4, and week 8. Sixty-five patients were included, and forty-nine patients completed the 8-week trial. Berberine led to significant declines in total cholesterol, low-density lipoprotein cholesterol, fasting serum insulin, and insulin resistance(all p <0.05) compared with placebo. Baseline body mass index and serum prolactin concentration could predict the effect of berberine on insulin resistance. Berberine adjunctive treatment may reduce the risk of glycolipid metabolic disturbances in patients with schizophrenia.